2007
DOI: 10.1111/j.1365-2591.2007.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on surface hardness and microstructure of mineral trioxide aggregate

Abstract: Under the conditions of this study, surface hardness of MTA was impaired in an acidic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
185
3
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(199 citation statements)
references
References 57 publications
10
185
3
1
Order By: Relevance
“…Furthermore, the structural changes of MTA after the application of hydrogen peroxide (H 2 O 2 ) solution as acidic conditions have been investigated using SEM and the EDX system (18)(19)(20)(21)(22)(23). Each report 4 presents different data and results, which is thought to be due to the differences in the concentrations of the H 2 O 2 solution, the reaction time, and the time lapse after MTA setting.…”
mentioning
confidence: 99%
“…Furthermore, the structural changes of MTA after the application of hydrogen peroxide (H 2 O 2 ) solution as acidic conditions have been investigated using SEM and the EDX system (18)(19)(20)(21)(22)(23). Each report 4 presents different data and results, which is thought to be due to the differences in the concentrations of the H 2 O 2 solution, the reaction time, and the time lapse after MTA setting.…”
mentioning
confidence: 99%
“…It could therefore be concluded that conventional GIC might be layered over partially set MTA after 45 minutes and could be used for single visit procedures (25). The microhardness of MTA is affected by many factors, such as the pH (26,27), humidity and setting time (28 In the 1-day groups, the microhardness decreased remarkably regardless of the presence or absence of a bonding agent. The dehydration of MTA surface due to air-drying before composite resin filling resulted in the prevention of moist curing and a significant decrease in the microhardness value.…”
mentioning
confidence: 99%
“…Namazikhahet al 14 stated that at an alkaline pH of7.4 the Vickers microhardness of MTA was 53.19 whichreduced radically as the pH was lowered.…”
Section: Discussionmentioning
confidence: 99%